Formulations of Organic Matter for Biodegridable Planting Bag - Chanan, Mochammad; Iriany, Aniek; Iriany, Atiek (International Journal of Engineering and Technology, 2019)
This research was aimed to generate an efficient and effective material formulation of planting bag using organic waste which could be applied to support the plant nursery technology. This research was conducted using completely randomized design with three times replication. The observable variables were: the chemical content of material including organic C, C/N, SOM, and N total. The variables of material quality were yield, tensile strength, and Valensky test. The result of this research indicated that the material composition of 25% water hyacinth: 50% straw: 25%Â banana sheath produced higher N total, organic C and organic matters. Then, the material composition of 50% water hyacinth: 25% straw: 25% banana sheath generate material quality with higher tensile strength (33N/cm2). While the material composition consisting of 25% water hyacinth: 25% straw: 50% banana sheath produced higher yield value (80%). Due to the material proportion of water hyacinth, straw, and banana sheath, it affected the decrease and increase of light intensity whether in all season. It means biodegradable planting bag potentially substitute polybag or in organic planting bag with satisfied physical and mechanical properties.Â Â